Genetic diversity and population structure of Brachiaria brizantha (A.Rich.) Stapf accessions from Ethiopia - Tegegn, Asheber; Kyalo, Martina; Mutai, Collins; Hanson, Jean; Asefa, Getnet; Djikeng, Appolinaire; Ghimire, Sita R. (National Inquiry Services Center, 2019)
Brachiaria is a tropical, warm-season grass native to Africa. It is an extensively cultivated forage in the tropics with proven benefits on livestock productivity. Brachiaria is well-known for high biomass production, animal nutrition, carbon sequestration, biological nitrification inhibition, soil conservation, and adaptation to drought and low fertility soils. However, the use of Brachiaria grass for fodder production in Africa has been little explored largely due to lack of cultivars suitable to different production environments. The exploration and use of natural diversity is fundamental for an efficient Brachiaria breeding program. We analysed genetic diversity and population structure of 112 Ethiopian Brachiaria brizantha accessions using 23 microsatellite markers. A total of 459 alleles were detected with an average polymorphic information content of 0.75 suggesting high discriminating ability of these markers. The molecular variance analysis showed a high contribution (86%) of within-cluster differences to the total variation. Three allelic pools revealed by STRUCTURE analysis in 112 accessions were in agreement with the clustering patterns seen in neighbor-joining tree and principal coordinates analyses. A core collection of 39 B. brizantha accessions was constituted. This study concludes a high genetic diversity of Ethiopian B. brizantha accessions and their importance in Brachiaria breeding programs.